UNDERSTANDING RECOUNT TEXT THROUGH EGRA IMPLEMENTATION - Tri Indah Rezeki; Rakhmat Wahyudin Sagala (STKIP Budidaya Binjai, 2022)
Experience, Generalization, Reinforcement, Application (EGRA) technique is suitable for teaching writing. Teaching writing using EGRA techniques executes the students are easier to develop stories based on their experiences. This study focused on investigating the implementation of the EGRA technique in understanding recount text by the students at SMPIT Al-Hijrah 2 Deli Serdang. Specifically, the objective of this study is to find out the effect of the EGRA technique on students' writing ability in recount text. This study employs a quasi-experimental design, including a pre-test and post-test control group design—the Eighth-grade students at SMPIT Al-Hijrah 2 Deli Serdang as the population of the study. The researchers selected two classes of Eighth-grade students as the sample of this study. The sample selection used random cluster sampling, specifically the Eight-grade Al-Karim as the experimental class, which consisted of 30 students, and the Eighth-grade VIII Al-Mughni as the control class, which consisted of 30 students. The experimental class was taught using the EGRA technique, and the control class was taught using the conventional method. The data of this study were analyzed by using t-test formula. The result from calculating the data showed that the implementation of EGRA was effective to be applied in teaching students of the Eighth-grade students at SMPIT Al-Hijrah 2 Deli Serdang in writing recount text. In other words, it was revealed that the use of EGRA technique was effective enough to enhance the students' understanding in writing recount text. While the application of the conventional method was not effective in improving students' ability to understand recount text.Keywords: Writing, EGRA Technique, Understanding a Recount text